Effectiveness of locally run conservation initiatives in north-east Peru. Issue 2 (1st May 2014) - Shanee, Noga; Shanee, Sam; Horwich, Robert H.
Abstract: Amazonas and San Martin are two of the most densely populated regions in rural Peru and have some of the highest deforestation rates in the country. They are also home to many threatened and endemic species and are considered a high priority for conservation. Under Peruvian law individuals and community groups can create private conservation areas and conservation concessions, and we evaluated the successes and challenges experienced in the creation and management of such areas, using direct observation, questionnaires and key-informant interviews. Our results show that far from being a problem for conservation many rural communities are actively promoting or participating in conservation initiatives on a local scale with landscape-level impacts. These initiatives include land protection, hunting control and reduced deforestation, thus providing effective solutions to threats. The main obstacles we identified in relation to such campesino (peasant farmer) conservation initiatives were the lack of access to support from governmental and non-governmental institutions and to economic resources to fund the extensive bureaucratic processes of registering protected areas. Many campesino communities bypass these restrictions through informal conservation initiatives.